Formation Of Indicators Of The Growth Period And The First Harvest Horn In Fiber F3plants (Texas Journal of Agriculture and Biological Sciences, 2024)
In this article, the positive results of the family obtained on the basis of cross-breeding of largeskinned ridges and varieties belonging to the type of G.barbadense L. were noted. In particular, the most positive result for the period of 50% pod opening was observed in the population Family-19/1, which showed that the model was 4.0 days earlier than the variety Surkhan-14. In addition, a positive result on the location of the first harvest branch was determined in the population of Family-19/1 (3.9±0.23), and it was found that the model was superior to the variety Surkhan-14 by 0.6 difference (4.5±0.22).